TRANSMIGRASI ETNIS BALI DI KECAMATAN SEPUTIH MATARAM (KAJIAN HISTORIS TERHADAP DINAMIKA RELASI TRANSFORMASI SOSIAL BERDASARKAN SISTEM KEKERABATAN TAHUN 1953-1969) - I Nyoman Sukma Aditya; Kuswono Kuswono (Swarnadwipa, 2021)
Transmigration is one form of a solution between the interests of society and the interests of the government. Efforts to level the population as well as the goal of controlling population explosions and poverty are part of government plans. Bali is one of the island's high numbers of inhabitants until they are also the target of the transmigration program. This study aims to find in depth the arrival of ethnic Balinese in Lampung, their ability to adapt and transformation relationships that occur in their kinship system. The results of this study were 1) The arrival of the Balinese ethnicity in Seputih Mataram in 1953-1969 through a series of long process. Starting from the preparation stage undertaken with certain conditions to the role of government in its implementation. Transmigration is considered as the community's need and the interests of the government in realizing social stability, 2) Adaptation of Balinese ethnicity in Seputih Mataram through a long series. Differences in natural conditions become obstacles are still found many wild animals not to mention they have to open land which at that time still like forest because there are still many big trees there. But that is not a barrier until finally they are able to create a new life pattern with a structured village, 3) Relation and social transformation of ethnic Balinese in Seputih Mataram, in this case a slight change. Although normatively they understand the concept of caste, but in reality caste is not an obstacle in interacting though there is still a high caste. The Balinese of Bali in Seputih Mataram are more flexible and open in accepting change.